Hubungan Faktor Lingkungan dengan Kejadian Kusta di Indonesia: Literature Review - Fazlul Nasrullah; Alviah Meszalunna; Rachelia Annisa Tomasa; Azzah Tira Syifa; Muhammad Hirafino Ardhi; Syeri Febriyanti (Pelantar Press, 2026)
Leprosy remains a public health problem in Indonesia, with new cases continuing to be reported each year. Environmental factors are believed to contribute to the incidence of leprosy. This article aims to analyze the relationship between environmental factors and the incidence of leprosy in Indonesia. This study utilizes a literature review design by examining 8 articles from Google Scholar and SINTA-indexed national journals published between 2021 and 2025. The results indicate that environmental factors are associated with the incidence of leprosy in Indonesia. The most dominant factors found to be associated were housing density and ventilation area, followed by air humidity, natural lighting, floor conditions and clean water sources